An unimportant insect pest with characteristic symptoms: Halticus apterus (Miridae) - Bozsik, András (Acta Agraria Debreceniensis, 2017)
Halticus apterus, a tiny mirid bug with jumping hind legs has not been taught in agricultural entomology courses in Hungary. However, the most detailed agricultural entomology text book, the “Handbook of Agricultural Entomology” briefly presents the pest. Although, it is common in Hungary, its damage is insignificant because of the low density; it can cause quality loss in feed crops only. Nevertheless, its special symptom – spottedness – is worth taking into consideration. The author has been studying pests and natural enemies of alfalfa for a long time (at least ten years), so he focused attention on this species. Occurrence of H. apterus was only sporadic in the alfalfa field, but it showed characteristic and frequent symptoms at a density of averagely three individuals per alfalfa plants in mixed plant associations at the studied field edge. By presenting the damage appearance and form, it was possible to make a more accurate description of H. apterus’symptoms, and with evaluating relevant European references, also the detailed entomological characterisation, economic importance and assessment of future risks have been achieved. As a difference to former descriptions, the special leaf spottedness of H. apterus does not consist of homogenous round spots but rather of spherical conglomerations of tiny whitish dots caused by the piercing and sucking mouthparts and the injected saliva